Subacute cutaneous lupus erythematosus and dermatomyositis associated with anti‐programmed cell death 1 therapy. (10th December 2018) - Marano, A.L.; Clarke, J.M.; Morse, M.A.; Shah, A.; Barrow, W.; Selim, M.A.; Hall, R.P.; Cardones, A.R.
Summary: Programmed cell death 1 (PD‐1) blockade has rapidly emerged as an effective therapy for a wide variety of metastatic malignancies. It has been associated with multiple immune‐related adverse effects, including cutaneous eruptions. We describe two patients with clinical and histological findings that were consistent with subacute cutaneous lupus erythematosus (SCLE) after receiving PD‐1 inhibitor therapy for metastatic lung cancer. We successfully treated our first patient with systemic and topical steroids, photoprotection and hydroxychloroquine. However, he subsequently developed dermatomyositis after continuing PD‐1 inhibitor therapy. Our second patient presented with a protracted course of a cutaneous eruption in spite of discontinuation of anti‐PD‐1 therapy and treatment with systemic corticosteroids and infliximab. This patient's SCLE resolved after the addition of topical steroids and photoprotection and discontinuation of anti‐tumour necrosis factor therapy. She and her oncology team decided to pursue non‐PD‐1 inhibitor treatment for lung cancer owing to a lack of tumour response. We add SCLE and dermatomyositis to the growing list of autoimmune complications of PD‐1 blockade. Our cases raise a number of questions, particularly in relation to the viability of continuing anti‐PD‐1 therapy after developing SCLE and the role of immunosuppressive therapy in patients with PD‐1 inhibitor‐associated connective tissue disease. What's already known about this topic? Programmed cell death 1 (PD‐1) blockade, which is rapidly emerging as a therapy for a wide variety of metastatic malignancies, has been associated with multiple immune‐related adverse effects. These include systemic autoimmune diseases such as colitis and thyroiditis in addition to numerous cutaneous adverse events. Cutaneous side‐effects of PD‐1 inhibitors most commonly reported in clinical trials include lichenoid reactions, eczematous dermatitis and vitiligo. What does this study add? We report two cases of PD‐1 inhibitor‐associated subacute cutaneous lupus erythematosus (SCLE), with one patient progressing to dermatomyositis with continued PD‐1 inhibitor treatment. In addition to being a novel cutaneous adverse event, we also demonstrate the possibility of development of multiple autoimmune diseases in one patient, which is different from classic drug‐related SCLE. We discuss the treatment challenges for patients with autoimmune skin disease receiving PD‐1 inhibitor therapy. Abstract : Linked Comment : Hunter. Br J Dermatol 2019; 181 :445–446 . Plain language summary available online